Electroanatomical Voltage and Morphology Characteristics in Postinfarction Patients Undergoing Ventricular Tachycardia Ablation. (August 2015) - Tsiachris, Dimitris; Silberbauer, John; Maccabelli, Giuseppe; Oloriz, Teresa; Baratto, Francesca; Mizuno, Hiroya; Bisceglia, Caterina; Vergara, Pasquale; Marzi, Alessandra; Sora, Nicoleta; Guarracini, Fabrizio; Radinovic, Andrea; et al.
<x xml:space="preserve">Abstract</x> Background— Catheter ablation is an important therapeutic option in postmyocardial infarction patients with ventricular tachycardia (VT). We analyzed the endo–epicardial electroanatomical mapping (EAM) voltage and morphology characteristics, their association with clinical data and their prognostic value in a large cohort of postmyocardial infarction patients. Methods and Results— We performed total and segmental analysis of voltage (bipolar dense scar [DS] and low voltage areas, unipolar low voltage and penumbra areas) and morphology characteristics (presence of abnormal late potentials [LPs] and early potentials [EPs]) in 100 postmyocardial infarction patients undergoing electroanatomical mapping–based VT ablation (26 endo–epicardial procedures) from 2010–2012. All patients had unipolar low voltage areas, whereas 18% had no identifiable endocardial bipolar DS areas. Endocardial bipolar DS area >22.5 cm2 best predicted scar transmurality. Endo–epicardial LPs were recorded in 2/3 patients, more frequently in nonseptal myocardial segments and were abolished in 51%. Endocardial bipolar DS area >7 cm2 and endocardial bipolar scar density >0.35 predicted epicardial LPs. Isolated LPs are located mainly epicardially and EPs endocardially. As a primary strategy, LPs and VT-mapping ablation occurred in 48%, only VT-mapping ablation in 27%, only LPs ablation in 17%, and EPs ablation in 6%. Endocardial LP abolition was associated with reduced VT recurrence and increased unipolar penumbra area predicted cardiac death. Conclusions— Endocardial scar extension and density predict scar transmurality and endo–epicardial presence of LPs, although DS is not always identified in postmyocardial infarction patients. LPs, most frequently located in nonseptal myocardial segments, were abolished in 51% resulting in improved outcome.